Comparison of Echocardiographic Patterns between Mild to Moderate and Severe CKD with type 4 Cardio renal Syndrome Patients (University Heart Journal, 2016)
Abstract not availableUniversity Heart Journal Vol. 11, No. 1, January 2015; 02